Atmospheric response to the annular solar eclipse of 26 December 2019 over Cochin, India. Issue 9 (1st November 2021) - Manoj, M.G.; C., Sivan; V., Rakesh; Rebello, Rejoy; S., Abhilash; K, Mohankumar
Highlights: Atmospheric response to annular solar eclipse of December 2019. Drastic reduction in incoming solar radiation and variations in meteorological variables. Mean PBL and Tropopause Heights were reduced by 50% and 5.5%. Detected the presence of internal gravity waves with periodicities of 40–60 min. Study useful for radiative transfer calculation and also for testing numerical models. Abstract: The rapid response of the atmosphere to the reduction in solar radiation during the annular solar eclipse on 26th December 2019 with maximum obscurity of 91.16% over Cochin, located in the southwest peninsular India, has been investigated. A suite of instruments encompassing an advanced VHF wind profiling Radar operating at 205 MHz, GPS radiosonde, and automatic weather station was employed to record the temporal and vertical variations in various meteorological parameters. Compared to the corresponding values averaged for two control days neighboring the eclipse day, the temperature, relative humidity, net radiation, pressure and wind speed at the surface were altered by −4.0 °C, +39.6%, −383.0 Wm −2, +0.62 mb, and −2.6 ms −1, respectively. The corresponding percentage variations are −13.6%, +71.0%, −67.0%, +0.06%, and −99.0% during the maximum phase of the eclipse, and approached close to the control-day values within about 2 h. Multiple temperature inversions as large as 1 °C were observed up to a height of about 7.3 km. The heights of mean planetary boundary layer (PBL) and tropopause were decreased by about 355 m (−50%) and 900 m (−5.5%), respectively during the peak of obscuration. Meanwhile, the vertical profiles of both the horizontal and vertical wind velocities demonstrate substantial reduction. The vertical wind dispersion, which characterizes the fluctuations in vertical air motion, was reduced by 34% in the PBL compared to its corresponding values on the control days. Subsequently, wavelet spectral analysis of the vertical wind yields a quasi-periodic oscillation indicating the presence of internal gravity waves with periodicities of 40–60 min in the lower altitudes up to 3 km during the eclipse day. Besides reporting the characteristic variations in various atmospheric parameters, the present study reveals the height-time variations in the vertical winds, a vital parameter of significance in the studies of convection, turbulence, and atmospheric waves.